2014
DOI: 10.1016/j.csr.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Morphospecies and taxonomic sufficiency of benthic megafauna in scientific bottom trawl surveys

Abstract: Scientific fisheries surveys routinely identify a large diversity of commercial and non-commercial benthic megainvertebrates that could provide useful information for Marine Strategy Framework Directive (MSFD) descriptors. Species is obviously the basic taxonomic level to which most ecological studies and theories refer. Identification at this level of organization is indeed always preferred over any other taxonomic level. Nevertheless, aggregation of species to higher taxonomic levels may be unavoidable somet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 52 publications
0
21
0
1
Order By: Relevance
“…Scaling at the genus level was done since identifications were patchy at the species level among stations (Brind'Amour et al, 2014). We chose to remove species found at only one station to allow better detection of the underlying community similarities (Clarke and Warwick, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Scaling at the genus level was done since identifications were patchy at the species level among stations (Brind'Amour et al, 2014). We chose to remove species found at only one station to allow better detection of the underlying community similarities (Clarke and Warwick, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is commonly taken in studies that use benthic imagery (e.g. James, Marzloff, Barrett, Friedman, & Johnson, ; Schlacher et al, ; Williams, Althaus, Barker, Kloser, & Keith, ), and has proven useful for characterizing benthic communities and detecting change (Brind'Amour et al, ). Hereafter, these morphospecies will be referred to as ‘species’.…”
Section: Methodsmentioning
confidence: 99%
“…They are assumed to represent species but were not officially taxonomically identified, as no physical samples were taken. This approach is commonly taken in studies that use benthic (Brind'Amour et al, 2014). Hereafter, these morphospecies will be referred to as 'species' .…”
Section: Introductionmentioning
confidence: 99%
“…On other temperate continental shelves like the Bay of Biscay or the English Channel, mixed mud-rock habitat is described and is further divided into different categories, depending on the size and abundance of the unconsolidated rocks involved, with different assemblages (Brind'Amour et al 2014). Within this study, the differences between mixed mud-rock at BA versus the other two sites similarly may be related to the difference of the size and abundance of the unconsolidated rocks.…”
Section: Mixed Mud-rockmentioning
confidence: 96%
“…Given these findings, 'mixed mud-rock' should be mapped as a distinct habitat characterized by low densities of a diversity of taxa, particularly sponges, gorgonians, anemones, and burrowing echinoderms. Since Brind'Amour et al (2014) have shown that this habitat can be divided in several categories, future studies should be designed to obtain thorough coverage of transition areas between consolidated rock and mud habitats to discern whether the different sizes of the interstitial rocks in the transition zone support distinct mega-invertebrate assemblages.…”
Section: Mixed Mud-rockmentioning
confidence: 99%